Similar Carcass Surface Microbiota Observed Following Primary Processing of Different Pig Batches - Braley, Charlotte; Fravalo, Philippe; Gaucher, Marie-Lou; Larivière-Gauthier, Guillaume; Shedleur-Bourguignon, Fanie; Longpré, Jessie; Thibodeau, Alexandre (Frontiers in Microbiology, 2022)
Bacterial contamination during meat processing is a concern for both food safety and for the shelf life of pork meat products. The gut microbiota of meat-producing animals is one of the most important sources of surface contamination of processed carcasses. This microbiota is recognized to vary between pigs from different farms and could thus be reflected on the bacterial contamination of carcasses at time of processing. In this study, the microbiota of 26 carcasses of pigs originating from different farms (i.e., batches) were compared to determine if an association could be observed between carcass surface microbiota (top and bottom) and the origin of slaughtered animals. The microbiota of the top and bottom carcass surface areas was analyzed by culturing classical indicator microorganisms (mesophilic aerobic bacteria, Enterobacteria, Escherichia coli, Pseudomonas, and lactic bacteria), by the detection of Salmonella, and by 16S rRNA gene sequencing. Culture results showed higher Enterobacteria, E. coli, and lactic bacteria counts for the bottom areas of the carcasses (neck/chest/shoulder) when compared to the top areas. Salmonella was not detected in any samples. Globally, 16S rRNA gene sequencing showed a similar composition and diversity between the top and bottom carcass areas. Despite the presence of some genera associated with fecal contamination such as Terrisporobacter, Escherichia-Shigella, Turicibacter, Clostridium sensustricto1, and Streptococcus on the carcass surface, sequencing analysis suggested that there was no difference between the different batches of samples from the top and bottom areas of the carcasses. The primary processing therefore appears to cause a uniformization of the carcass global surface microbiota, with some specific bacteria being different depending on the carcass area sampled.